A case of Q fever after liver transplantation. Issue 5 (12th July 2017) - Petty, Lindsay A.; Te, Helen S.; Pursell, Kenneth
Abstract: Coxiella burnetii, the causative agent of Q fever, is a zoonosis that causes both acute and chronic disease in humans. Few cases have been reported in solid organ transplant recipients, and this case highlights the need to include Q fever in the differential diagnosis for fever of unknown origin in solid organ transplant hosts.